6 - The Nigerian University System, Corruption and Erosion of the Public Good - Ibrahim, Jibrin (Journal of Higher Education in Africa, 2022)
This article examines the nature, causes and implications of the decline of the public good within Nigeria’s university system over the past three decades. In that period, there has been a significant shortfall in the finances of the university system from federal and state governments, creating the material basis for its inability to recruit, retain and manage quality academic and non-academic staff. Essentially, it highlights how the self-interest of academics, expressed through their powerful union, the Academic Staff Union of Universities (ASUU), has engaged in a struggle with government to improve the remuneration of academics rather than the quality of academic services. At the same time, corruption has sapped the system and led to significant levels of exploitation of students, in general, and the sexual harassment of female students. The public good within the university system is rooted in the constitutional provision that directs governments to provide quality and free education at all levels. But governments have failed in this mission, and families have had to pay for their children’s quality education. This outcome has created massive inequality, with only the wealthy able to ensure quality education for their children, usually abroad. This has weakened the commitment of those in authority to push for the return of quality education at the national level. The result is that the Nigerian state appears to have provoked a class struggle in which poorly educated youth and the lump n classes are marginalised and excluded from the ladder of social mobility.